Kualitas Hidup Pasien Stroke dalam Perawatan Palliative Homecare - Ulfah N Karim; Erika Lubis (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Stroke is a neurological deficit multi complex disease that causes physical or mental disability can affect all aspects of an individual's life, including the quality of life of patients. Quality of life related to the welfare of patients and families with the provision of Palliative homecare Phenomenological study was conducted to explore in depth the quality of life of patients in palliative care homecare. Participants in this study with 13 respondents using purposive sampling technique. Themes related to the quality of life is domains includes physical activity, diet, memory and concentration, physical mobility, speech, pain, sleep and rest. Psychological domains include self-image, motivation of life, happiness and sadness. Among other social domains of social change include changes in the social function and the role change. Quality of life domains increased physical activity, diet, mobilization of physical and speech. Quality of life increased in the psychological domains motivation alive, happy feelings. Quality of life increased in the social domains changes in social function. This study shows that the quality of life patients stroke increasing and study recommended importance further research is important and palliative care as an intervention homecare nursing which plays an important role for improving the quality of life stroke patient. This study shows that the quality of life patients stroke increasing and study recommended importance further research is important and palliative care as an intervention homecare nursing which plays an important role for improving the quality of life stroke patient.